Damage Evolution of Concrete Piles Mixed with Admixtures in Marine Corrosion and Freeze-Thaw Environment. (18th September 2021) - Li, Yan; Li, Bing; Zhang, Lianying; Ma, Chao
Abstract : Marine corrosion and freeze-thaw environment will bring serious damage to marine concrete structures, leading to affect the safety and service life of structures. With the help of artificial climate and environment simulation laboratory, the variation of the compression strength and elastic modulus of concrete with the number of freeze-thaw cycles and corrosion time under the corrosion and freeze-thaw environment is studied. The results show that both of them firstly increase and then decrease with corrosion time. When the corrosion time is 270 d and the freeze-thaw time is 90 times, the strength of concrete decreases by 13% and the elastic modulus decreases by 5%. Then, based on the theory of damage mechanics, the damage evolution and constitutive model of concrete under the marine corrosion and freeze-thaw environment are established. Compared with the experimental results, it is found that the model can well describe the damage evolution characteristics of concrete under marine corrosion and freeze-thaw environment. Finally, a numerical model is established on the basis of elastic modulus and strength degradation model of concrete under marine corrosion and freeze-thaw environment. Elevated pile caps of concrete pile component are taken as an example to analyze the process of damage, and the change rules of displacement, deformation, and damage of concrete pile are obtained.